1500Determinants of dietary behaviour and physical activity in Australian adolescents. (2nd September 2021) - Marjanovic, Sandra; Munasinghe, Sithum; Sperandei, Sandro; Jani, Hir; Conroy, Elizabeth; Freebairn, Louise; Page, Andrew
Abstract: Background: The increased prevalence of obesity, unhealthy diet and sedentary lifestyles among Australian adolescents has become a public health concern. This study investigated the associations between socio-economic status, screen-time, social networks, sleep, and wellbeing and subsequent health behaviours. Methods: A cohort of 582 adolescents aged 13-19 years from Sydney were prospectively followed for 22-weeks (8 November 2019 – 19 April 2020). Study factors were collected via mobile phone app using weekly ecological momentary assessments (EMAs). Multi-level mixed effects logistic regression model assessed associations between baseline characteristics of participants, socio-economic status, screen-time, sleep, and wellbeing and subsequent dietary behaviour and physical activity. Results: TV watching (odds ratio [OR]=1.22, 95% CI: 0.98-1.5), social media and internet use (OR = 1.22, 95% CI: 0.97-1.53) were associated with fast food consumption. Participants who spent more than four hours a day on social media were also less likely to be physically active for ³60 minutes (OR = 0.75, 95% CI: 0.6-0.94). Fast food consumption was associated with lower vegetable (OR = 0.61, 95% CI: 0.43-0.85) and fruit intake (OR = 0.78, 95% CI: 0.61-1.01), and was also more prevalent in participants with a job (OR = 1.42, 95% CI: 1.09-1.86). There was no substantial effect of psychological distress, positive emotions, social relationships and sleep on any health behaviour. Conclusions: The present study has shown that lifestyle behaviours had a stronger effect on dietary behaviour and physical activity than some of the socio-demographic factors. Key messages: Future studies with a balanced sample in terms of sex, age and cultural background are needed.